Crescimento, composição fitoquímica e efeito genotóxico do óleo essencial em alecrim (Rosmarinus officinalis L.) sob diferentes períodos de salinidade - Pinheiro, Suany Maria Gomes (2016)
Rosmarinus officinalis L. is a species that has stood out for its intense popular use, the main product the essential oil. The work was ainmed determine the effect of sa-linity on the biomass period, content, yield, phytochemical composition and genotoxi-city of essential oil of rosemary.Dois experiments sheets were simultaneously per-formed between June 3, 2014 to December 12, 2015, the experiments were per-formed in the department of Plant Science at the Federal University of Santa Maria. In the first experiment, the control (T1) was employed in a nutrient solution with elet-rical conductivity (EC) of 1.0 dSm-1 and the other four treatments (T2, T3, T4, T5) was used with a nutrient solution conductivity electric 5,0 dSm-1. T2 plants were submitted to the salt solution for a period of 140 days after planting (DAP) in T3 to 150 in the 160 T4 and T5 to 170 DAP. All plants were collected on 12 December 2014 complet-ing a period of 190 days. The period in which the plants remained under saline condi-tions before the collection was 50, 40, 30 and 20 days in T2, T3, T4 and T5, respec-tively. In the second experiment it was also compared four periods of salinity (CE 5.0 dSm-1) and control (CE 1.0 dSm- 1). The planting was done on the same day of the experiment I and the supply of saline solution began on the same day of the first trial, but the harvest was delayed in order to increase the periods in which the plants re-mained in saline conditions. All plants were collected on 12 February 2015. Thus, the salinity period before the collection was 110, 100, 90 and 80 days for treatments T2, T3, T4 and T5, respectively. In both experiments the experimental design was ran-domized with five replications. The Extraction of oil from the leaves by hydrodistilla-tion in Clevenger was performed and then performed gas chromatography. The es-sential oil was evaluated for antiproliferative and genotoxic effects in cells of Allium Cepa at a concentration of 0.20 % for the oil of plants grown in different periods of salinity collected at 190 after planting. The biomass production data and essential oil were subjected to analysis of variance with polynomial regression and other data were compared by Scott-Knott test (p <0.05). The results showed that the salinity period through a nutrient solution with electrical conductivity of 5 dS m-1 linearly re-duces biomass, content and essential oil yield of rosemary plants in soilless culture. The major compounds of the essential oil were camphor, 1.8 cineol, verbenone, α-pinene and β-myrcene. And this in turn was not genotoxic nor showed significant an-tiproliferative effect, except that obtained from the plants that remained for a longer period of exposure to salinity, which inhibited cell division of Allium Cepa.